Dilemmas in economic theory : persisting foundational problems of microeconomics - Mandler, Michael (Oxford University Press, 2001)
By examining the development of economics in the 20th century, this book argues that the breakthroughs of post-World War II general equilibrium theory and its rejection of utilitarianism and marginal productivity have been misunderstood.